Changes in soil microbial biomass and organic C pools improve the sustainability of perennial grass and legume system under organic nutrient management - Rai, Arvind Kumar; Basak, Nirmalendu; Dixit, Anoop Kumar; Rai, Suchit Kumar; Das, Sanjoy Kumar; Singh, J. B.; Kumar, Sunil; Kumar, T. Kiran; Chandra, Priyanka; Sundha, Parul; Bedwal, Sandeep (Frontiers in Microbiology, 2023)
The perennial grass-legume cropping system benefits soil because of its high biomass turnover, cover cropping nature, and different foraging behaviour. We investigated the response of soil organic carbon (SOC) pools and their stock to organic and inorganic nutrient management in Guinea grass and legume (cowpea–Egyptian clover) cropping system. Depth–wise soil samples were collected from after harvesting the Egyptian clover. Based on ease of oxidation with chromic acid, different pools SOC oxidizable Walkley and Black C, very labile, labile, less labile, non-labile; and dissolve organic C (DOC), microbial biomass C (MBC) and total organic C (TOC) in soils were analyzed for computing several indices of SOC. After ten years of the crop cycles, FYM and NPKF nutrient management recorded greater DOC, MBC, SOC stocks and C sequestration than the NPK. Stocks of all SOC pools and carbon management index (CMI) decreased with soil depth. A significant improvement in CMI, stratification ratio, sensitivity indices, and sustainable yield index was observed under FYM and NPKF. This grass-legume intercropping system maintained a positive carbon balance sequestered at about 0.8 Mg C ha–1 after ten years without any external input. About 44-51% of the applied carbon through manure was stabilized with SOC under this cropping system. The DOC, MBC and SOC in passive pools were identified for predicting dry fodder yield. This study concludes that the application of organics in the perennial grass-legume intercropping system can maintain long-term sustainability, enhance the C sequestration and offset the carbon footprint of the farm enterprises in the semi-arid, rainfed–irrigated agro-ecologies.